Changes Social of Environmental Education in Indigenous Peoples of the Jungle Jambi Province, Indonesia - Syafrizal Syafrizal; Meyniar Albina; Indrawati Indrawati; Latansa Hafizotun; Ria Maharani (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research aims to reveal the change and continuity of environmental education in the Indigenous people of the jungle Jambi Province, Indonesia. The method used was qualitative research method with the type of phenomenological research. The subjects of this study were the indigenous people of the jungle, namely: Temenggung, Tengganai, traditional leaders, and traditional youth. Data was collected by participatory observation and in-depth interviews using an unstructured interview draft. Data analysis was carried out using techniques: data reduction, display, and verification. The results of this study were (1) Changes in Environmental Education in the Indigenous people of the jungle Indigenous Peoples of Jambi Province referring to a sociological perspective could be categorized as social dynamics. Changes in the local jungle community have a social statistics category. The category is most of the jungle population which recognizes the oneness of gods who take good care of nature without any destruction from humans. It aims to sustain a prosperous life in the eyes of the jungle tribe (2) The continuity of environmental education in the jungle community was based on historical facts that were easily refuted. The sustainability of this environmental education was based on the community's awareness, solidarity, and survival. Indigenous people of the jungle believe that the forest is their home. The continuity of Indigenous people of the jungle environmental education occurs in two areas, structural or customary law and cultural education within the family.